PEMANFAATAN LIMBAH SERBUK HASIL OLAHAN KAYU SEBAGAI BAHAN PAPAN PARTIKEL DI UKM AISYAH MEBEL PALANGKA RAYA - Luqman Hakim; Jhon Wesly Manik; Dita Monita (LP2M STP Mataram, 2022)
Excessive use of wood can cause the amount of wood to be cut to increase as a result, wood is increasingly difficult to obtain. It should be realized that the use of forest products through the processing industry must begin to be observed and efforts must be made to use raw materials that must be able to be processed and produce useful and valuable products, even optimizing materials and minimizing waste or being environmentally friendly. The wood and non-timber waste is used for recycled products that can provide economic value benefits for the community. The raw material for particleboard comes from the rest of the wood processing in the sawmill industry, so it doesn't require high raw material requirements. The activity of utilizing processed wood powder waste is carried out at UKM Aisyah Furniture, Palangkaraya. The process of making particle board made from sawdust can use fox glue. The distribution of particles and adhesive that spreads evenly tends to get a more even board density. Knowledge of the utilization of wood-processed powder waste can be used to utilize wood-processed sawdust waste so that it has economic value